Institutional investment in Central and Eastern Europe: investment criteria of Western portfolio managers - Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This study provides detailed evidence on the transistion state of Central and Eastern Europe (CEE) countries. It draws on data from a survey conducted among portfolio managers of Western investment funds thereby making use of the knowledge of experts in CEE markets. The approach of the study is two-fold : First, criteria for portfolio investment and current barriers to higher investment in CEE countries are identified. Second, the CEE portfolio structure is explained making use of detailed grading data from the survey. The results suggest that a reduction in general and macroeconomic risk tends to increase investment and that the potential of high returns and low risk from the setting of financial markets contributes to signifficantly higher investment in some countries.
Keywords: G11; G23; O10; 330; Central and Eastern Europe; institutional investors; portfolio investment; Institutioneller Anleger; Portfolio-Investition; Anlageverhalten; Schätzung; Westliche Staaten; Osteuropa